Menguak Makna Laba Pedagang Sayur Keliling (Balijjah) Laki-Laki Dalam Perspektif Nilai Spritual - Auliyah, Robiatul; Angraini, Merie Satya (Ulumuna: Jurnal Studi Keilsman, 2024)
This study aims to uncover the awareness of the meaning of "profit" from the male side of the vegetable sellers or commonly referred to as the balijjah as the Madurese are according to the two informants' understanding. This research is a qualitative research with a phenomenological approach as an answer digger guide which is included in the type of transcendental phenomenology that focuses on individual awareness of each of the two vegetable vendors. The findings of this study state that profit is interpreted as material that is building a house is a manifestation of the results of selling vegetables and improving the economy to meet family needs. Then profit with spiritual value by not profiting too much profit for the smooth running of the commodity keeping in mind the obligation to worship can lead to unexpected success. Then profit as a form of social feeling that can help and make it easier for mothers or students to get cooking ingredients while providing a way of opportunity for those who need work.